Circulating free T3 associates longitudinally with cardio-metabolic risk factors in euthyroid children with higher TSH - Carreras-Badosa, Gemma; Puerto-Carranza, Elsa; Mas-Parés, Berta; Gómez-Vilarrubla, Ariadna; Cebrià-Fondevila, Helena; Díaz-Roldán, Ferran; Riera-Pérez, Elena; de Zegher, Francis; Ibañez, Lourdes; Bassols, Judit; López-Bermejo, Abel (Frontiers in Endocrinology, 2023)
Introduction: Thyroid hormones play major roles in the regulation of body composition and metabolism, and therefore the relation between thyroid hormones and cardio-metabolic risk has been extensively studied in adults. In this study we aimed to test whether free triiodothyronine (fT3) associates longitudinally with cardio-metabolic risk factors in euthyroid children. Methods: Prospective study cohort of 599 apparently healthy school-age children assessed at baseline (mean age 8.1 ± 2.1 years old), of whom 270 children were also assessed at follow-up (4 years later). Circulating TSH, fT4 and fT3 were measured, and cardio-metabolic risk was assessed by means of body mass index (BMI), waist circumference, visceral fat (by ultrasound), blood pressure, circulating lipids, and HOMA-IR index, both at baseline and at follow-up. Results: All studied children had normal thyroid function tests. Independent associations between baseline fT3 and both baseline and follow-up BMI, systolic blood pressure, mean arterial blood pressure, triglycerides and HOMA-IR were found using multivariate regression analysis (adjusting for sex and baseline age and BMI). Analyses of effect sizes showed that for each 1 unit-increase in baseline fT3 (pg/ml), follow-up BMI-SDS increased by 0.31 units (z-score) and systolic blood pressure by 6.6 units (mmHg). The observed longitudinal associations were more robust in children belonging to the upper TSH tertile who showed higher TSH levels and were characterized by weighing more and having the highest fT3 levels. In these children, for each 1 unit-increase in baseline fT3 (pg/ml), follow-up BMI-SDS increased by 0.67 units (z-score) and systolic blood pressure by 10.2 units (mmHg). Conclusions: Circulating fT3 associate longitudinally with cardio-metabolic risk factors in euthyroid children with higher TSH. The observed associations of thyroid hormones in these children could conceivably respond to a homeostatic attempt to reduce their cardio-metabolic risk.